Natural history of Charcot‐Marie‐Tooth disease during childhood. Issue 3 (22nd September 2017) - Cornett, Kayla M.D.; Menezes, Manoj P.; Shy, Rosemary R.; Moroni, Isabella; Pagliano, Emanuela; Pareyson, Davide; Estilow, Timothy; Yum, Sabrina W.; Bhandari, Trupti; Muntoni, Francesco; Laura, Matilde; Reilly, Mary M.; et al.
Abstract : Objective: To determine the rate of disease progression in a longitudinal natural history study of children with Charcot‐Marie‐Tooth (CMT) disease. Methods: Two hundred six (103 female) participants aged 3 to 20 years enrolled in the Inherited Neuropathies Consortium were assessed at baseline and 2 years. Demographic, anthropometric, and diagnostic information were collected. Disease progression was assessed with the CMT Pediatric Scale (CMTPedS), a reliable Rasch‐built linearly weighted disability scale evaluating fine and gross motor function, strength, sensation, and balance. Results: On average, CMTPedS Total scores progressed at a rate of 2.4 ± 4.9 over 2 years (14% change from baseline; p < 0.001). There was no difference between males and females (mean difference, 0.5; 95% confidence interval [CI], −0.9 to 1.9; p = 0.49). The most responsive CMTPedS items were dorsiflexion strength (z‐score change, −0.3; 95% CI, −0.6 to −0.05; p = 0.02), balance (z‐score change, −1.0; 95% CI, −1.9 to −0.09; p = 0.03), and long jump (z‐score change, −0.4; 95% CI, −0.7 to −0.02; p = 0.04). Of the most common genetic subtypes, 111 participants with CMT1A/ PMP22 duplication progressed by 1.8 ± 4.2 (12% change from baseline; p < 0.001), 9 participants with CMT1B/ MPZ mutation progressed by 2.2 ± 5.1 (11% change), 6 participants with CMT2A/ MFN2 mutation progressed by 6.2 ± 7.9 (23% change), and 7 participants with CMT4C/ SH3TC2 mutations progressed by 3.0 ± 4.5 (12% change). Participants with CMT2A progressed faster than CMT1A (mean difference, −4.4; 95% CI, −8.1 to −0.8; p = 0.02). Children with CMT1A progressed consistently through early childhood (3–10 years) and adolescence (11–20 years; mean difference, 1.1; 95% CI, −0.6 to 2.7; p = 0.19), whereas CMT2A appeared to progress faster during early childhood than adolescence (mean difference, 10.0; 95% CI, −2.2 to 22.2; p = 0.08). Interpretation: Using the CMTPedS as an outcome measure of disease severity, children with CMT progress at a significant rate over 2 years. Understanding the rate at which children with CMT deteriorate is essential for adequately powering trials of disease‐modifying interventions. Ann Neurol 2017;82:353–359